2017
DOI: 10.4103/jfmpc.jfmpc_129_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparing depressive symptoms in teenage boys and girls

Abstract: Introduction:Symptoms of depression vary between the males and females. Depressed men show behaviors such as irritability, restlessness, difficulty in concentrating, and instead of the usual behaviors. Sleep disturbance is a common symptom in depressed men. Men are less likely to go to doctors and unconsciously show other behaviors such as anger instead of the sadness. It seems that considering depression as “feminine” is a great injustice toward male patients whom their illness will not be diagnosed nor treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…As expected, our study showed that the prevalence of depression was highest in females than males and the older adolescents than younger adolescents, which were in agreement with the reported prevalence rates of depression from adolescents in the general populations, cancer patients, as well as refugees and asylum seekers and [ 42 44 ]. The possible reasons for the gender differences in the prevalence of depression include adverse experiences in childhood and adolescence, the sociocultural roles of adverse events (psychological trauma), sexual abuse and the variations in coping skills [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…As expected, our study showed that the prevalence of depression was highest in females than males and the older adolescents than younger adolescents, which were in agreement with the reported prevalence rates of depression from adolescents in the general populations, cancer patients, as well as refugees and asylum seekers and [ 42 44 ]. The possible reasons for the gender differences in the prevalence of depression include adverse experiences in childhood and adolescence, the sociocultural roles of adverse events (psychological trauma), sexual abuse and the variations in coping skills [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…Sex is a major predictor of an individual's susceptibility to mental disease. For instance, females are more susceptible than males to develop anxiety and depression during adolescence (about 70%), which may persist for lifetime (Khesht-Masjedi et al, 2017). These mental disorders seem related to environmental disruption of developmental programs, related to genetic predispositions, most likely involving a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…However, any competent explanation of such difference should take into account the social context in which such events were experienced. For example, Iranian female teenagers generally experienced a higher degree of distress symptoms (Javadi, Jourabchi, Shafikhani, & Tajik, 2017), which might become entangled with their higher vulnerability to experience selfdegrading feelings of guilt and punishment during depressive moods (Khesht-Masjedi, Shokrgozar, Abdollahi, Golshahi, & Sharif-Ghaziani, 2017). This compromised situation might heighten their willingness to take their own lives, particularly when family relations and interpersonal experiences, instead of being a sanctuary during childhood, became a liability.…”
Section: Discussionmentioning
confidence: 99%